MODEL PENGENDALI SUHU PEMANAS AIR UNTUK PEMBUAT KOPI MENGGUNAKAN KONSEP INTERNET OF THINGS (IoT) - Susanto, Susanto; Daru, April Firman (UNIVERSITAS STEKOM, 2025)
The quality of coffee is determined by its taste, aroma, and flavor. These three factors are key attributes influencing the human multisensory perception of coffee. This multisensory perception can be affected by various factors, including the brewing method, roasting temperature, coffee variety, storage conditions, grinding process, and the quality of the brewing water. Manual coffee preparation poses the risk of water temperatures deviating from recommended standards. Therefore, this study proposes an efficient control device in the form of an IoT-based automatic coffee heater. The system integrates a temperature sensor to measure water temperature, an ESP32 microcontroller for processing, and the AI2 App Inventor application for control and monitoring purposes. The device is designed to maintain coffee at the ideal temperature range, preserving its freshness and sensory quality as if it had just been brewed. This is critical because the brewing temperature is a major factor influencing the flavor profile of coffee. According to the Specialty Coffee Association of America (SCAA), the recommended water temperature for brewing coffee is 92°C, with a technical requirement for beverages served to consumers to be no lower than 80°C and no higher than 85°C. The ideal serving temperature for coffee is between 62.8°C and 68.3°C. Based on comprehensive system testing, the device achieved an average success rate of 98.97%.